Deteksi Keberadaan Antigen dan Antibodi terhadap Equine Influenza pada Kuda Impor dari Belanda - Alzab, Amrie Muhammad; Murtini, Sri; Pribadi, Eko Sugeng (Universitas Al Azhar Indonesia, 2024)
Equine Influenza (EI) is a highly contagious respiratory infection disease in equidae caused by two subtypes of Influenza A Virus (H7N7 and H3N8). Indonesia is recently importing high amounts of horses from The Netherlands intended for equestrian sports, pets, and breeders. This study was aimed to discover the presence of Equine Influenza Virus (EIV) and antibody titres against EIV in imported horses from the Netherlands using Reverse Transcription-Polymerase Chain Reaction (RT-PCR) and Enzyme-linked Immunosorbent Assay (ELISA) techniques. The results obtained were then compared to imported horses’ data. A total of 199 nasopharyngeal swabs and 55 blood samples were collected. The results showed no material genetic of EIV was found in horses imported from the Netherlands, not all recently imported horses had antibodies against EIV, it’s indicated that the imported horses need to be measured the antibody post vaccination before arrived in Indonesia.Keywords - Horse, Equine Influenza, The Netherlands, PCR, ELISA